Influences of in-plane and out-of-plane fiber waviness on mechanical properties of carbon fiber composite laminate. (July 2018) - Wu, Chenjun; Gu, Yizhuo; Luo, Liang; Xu, Peng; Wang, Shaokai; Li, Min; Zhang, Zuoguang
Based on the curing process of carbon fiber/epoxy prepreg with autoclave, two kinds of unidirectional carbon fiber laminates with in-plane and out-of-plane waviness were fabricated by rolling prefabricated out-of-plane waviness and inserting prepreg strip, respectively. Fiber waviness defects in composites were characterized by waviness ratio. The specimens containing fiber waviness were successfully prepared with almost the same fiber content and low porosity. The influences of fiber waviness with different waviness ratio on tensile, compressive, and charpy impact properties of unidirectional laminates were studied, and the corresponding failure modes were observed. The mechanism of the effects of fiber waviness on mechanical properties was discussed. The experimental results show that tensile property and compressive property decrease by in-plane buckling and out-of-plane wrinkling, especially with large waviness ratio. Reduction of 33.0% of compressive strength with out-of-plane wrinkling is seen in the case of 0.037 waviness ratio, while 25.4% reduction is obtained for in-plane buckling under 0.038 waviness ratio. Charpy impact strength decreases by in-plane buckling, whereas increases by out-of-plane wrinkling. Failure morphologies of various specimens are changed by fiber waviness, which are consistent with the mechanical degradation. In addition, there are some differences on the sensitivity of mechanical properties to different types of fiber waviness. Tensile strength is more sensitive to in-plane buckling in comparison with out-of-plane wrinkling, and compressive property is more sensitive to out-of-plane wrinkling.